Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1152/ajpendo.90534.2008
|View full text |Cite
|
Sign up to set email alerts
|

Ciglitazone, a PPARγ agonist, ameliorates diabetic nephropathy in part through homocysteine clearance

Abstract: Sen U, Rodriguez WE, Tyagi N, Kumar M, Kundu S, Tyagi SC. Ciglitazone, a PPAR␥ agonist, ameliorates diabetic nephropathy in part through homocysteine clearance. Am J Physiol Endocrinol Metab 295: E1205-E1212, 2008. First published September 9, 2008 doi:10.1152/ajpendo.90534.2008.-Diabetes and hyperhomocysteinemia (HHcy) are two independent risk factors for glomeruloslerosis and renal insufficiency. Although PPAR␥ agonists such as ciglitazone (CZ) are known to modulate diabetic nephropathy, the role of CZ in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…These contradictions could be caused by differences in animal strains, samples obtained, and cell types examined, as well as the fact that diabetes treatment affects MMP expression (126). Some models show that decreased MMP activity, particularly of MMP-2 and MMP-9, ameliorate kidney lesions (107,114,144,150), whereas in other models maintenance of MMPs, namely, MMP-1 and in some cases even MMP-9, is associated with improvement (see Table 2) (4,34). Similarly contradictory, TIMP-3 was elevated in diabetes, but TIMP-3 null mice actually had worsened fibrosis and increased activation of MMP-2 (55,57).…”
Section: Mmps In Renal Pathologymentioning
confidence: 99%
“…These contradictions could be caused by differences in animal strains, samples obtained, and cell types examined, as well as the fact that diabetes treatment affects MMP expression (126). Some models show that decreased MMP activity, particularly of MMP-2 and MMP-9, ameliorate kidney lesions (107,114,144,150), whereas in other models maintenance of MMPs, namely, MMP-1 and in some cases even MMP-9, is associated with improvement (see Table 2) (4,34). Similarly contradictory, TIMP-3 was elevated in diabetes, but TIMP-3 null mice actually had worsened fibrosis and increased activation of MMP-2 (55,57).…”
Section: Mmps In Renal Pathologymentioning
confidence: 99%
“…In disease condition, such as in diabetic nephropathy, Hcy disposal and clearance are impaired and therefore accumulate in the body, resulting in increase of plasma and tissue levels of Hcy (43). This, in turn, causes renal microvascular impairment and vasoconstriction (37), which lead to renal volume retention and further accumulation of Hcy (38). This is a vicious cycle and is often associated with chronic renal failure.…”
Section: K Wt 2k Wtmentioning
confidence: 99%
“…Previously, we have reported that reduction in renal function leads to an increased plasma Hcy level (36,38). The elevated plasma Hcy, in turn, causes renal insufficiency, which leads to a vicious cycle (22).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This seemingly paradoxical effect has been demonstrated with other hormones and growth factors, such as insulin (11), which decreases plasma levels of amino acids by increasing tissue uptake. Previously, we demonstrated elevated tissue levels of Hcy in the kidney (37) and heart tissue (33) of hyperhomocysteinemic mice with alloxan-induced diabetes mellitus. We also demonstrated that the level of cystathione ␥-lyase (CSE), an enzyme responsible for conversion of Hcy to H 2 S, a potent antioxidant, vasorelaxant, and antihypertensive agent, was decreased in the kidney of another model of HHcy, the uninephrectomized cystathionine ␤-synthase heterozygous (CBSϩ/Ϫ) mice (36).…”
mentioning
confidence: 94%